Atividade inseticida do extrato bruto etanólico de persea americana (lauraceae) sobre larvas e pupas de aedes aegypti (diptera, culicidae) - CARVALHO, George Harrison Ferreira de (2011)
In the search for new alternatives for control of Aedes aegypti, in view of its resistance to chemical insecticides in use, research on plant substances has been increasing, due to be degradable and less toxic to vertebrates. The aim of this study was to evaluate the insecticidal effect of crude ethanol extract (cee) of bark of Persea americana Mill, on larvae and pupae of Ae. aegypti in the laboratory and field. After obtaining this cee was dissolved in dimethyl sulfoxide (DMSO), thus obtaining the test solution. For each test, and repetition, in both laboratory and field were used 100 larvae of the 1st, 2nd, 3rd and 4th instars and 100 pupae too. The same amount of larvae and pupae was used for the groups positive and negative controls, performed respectively with temephos at 1 ppm and 1.6% of the DMSO. Both the laboratory bioassays and field were conducted with key artificial urban tire, glass and plastic. The results showed the insecticidal activity of the cee P. americana larvae and pupae of Ae. aegypti, both in laboratory and field. There was 100% mortality of the larvae of the 1st and 2nd instars in the laboratory at a dose of 5 ppm and field at a dose of 10 ppm. In the laboratory the LC50 and LC90 were respectively 7.2 and 19.3 ppm for 3rd instar, 6.6 and 15.4 ppm for 4th instar and 93.6 and 158.7 ppm for pupae. Following the same order, in the field, the LC50 and LC90 were 27.8 and 51.3 ppm plows the 3rd instar, 23.8 and 46.9 ppm for the 4th instar and 145.3 and 261.9 ppm for the pupae. The most important factor of this study was the effect pupicida of P. americana, because it is very rare to find this effect on other products, both natural and synthetic.Tests acute oral toxicity in rats were conducted to cee this plant that proved to be nontoxic according to norms (Acute Toxic Class Method - OECD 423) for products of plant origin.